A MOSFET type sensor for oxygen sensing using LaF3 as a gate material - CHOI, SK; YI, CW; CHO, WI; CHO, BW; JU, JB; YUN, KS; YAMAZOE, N (Elsevier BV, 1993)
A MOSFET type sensor for O2 gas detection with a gate material of LaF3 film deposited on an ordinary n-channel MOSFET was fabricated. The LaF3 film of 800 angstrom thickness and the Pt film of 500 angstrom thickness were deposited, sequentially, by the e-beam evaporation method. The amount of drain current was decreased by about 130 muA with O2 gas and the response and regeneration times of this sensor were 1 and 17 min at 80-degrees-C, respectively, when measured by the constant voltage method (V(D) = 3 V, V(G) = 0 V). In the constant voltage method, the higher the operating temperature, the shorter the response time. As oxygen gas was injected, the gate voltage of this sensor was shifted to 30 mV and its response time was 3.5 min with the constant current method (I(D) = 500 nA). When the oxygen concentration was 0.05% in nitrogen, the gate voltage ratio of the oxygen gas sensor approached 0.5.